The Impact of Financial Performance of Stock Prices of Jordanian Islamic Banks (During Period from 2010 to 2018) - Al-Qudah, Hanan Ahmad (International Journal of Economics and Financial Issues, 2020)
This study aims to identify the impact of financial performance of stock prices of Jordanian Islamic Banks which are listed on the ASE. In order to achieve the goal of this study, the researcher collected and analyzed data from two banks, as a study sample, during the period (2010 to 2018), using the panel data method. The study the measures the financial performance in financial ratios which were represented in (return on assets, return on equity, change in earnings per share) and were measured at stock prices. The results of the study showed that there is a discussion of the results of the main variable. Based on the results of the previous statistical tests, it was found that there is a significant statistical significance between the financial performance of the Islamic banks represented by (return on assets, return on equity, change in earnings per share); therefore, we believe that this result is consistent with economic studies and financial and market analyzes, therefore, stock prices are an indicator of the health of growth in the financial markets, and evidence of stock prices for banks which constitute the basis of stability and the functioning of markets, all due to the profitability of banks and stability of financial performance. The researcher recommended that the Jordanian Islamic banks seek to increase their profits and improve their financial performance and strive for excellence in their activities in order to win the trust and preservation of customers. He also recommended Islamic banks to distribute dividends on a periodic basis to shareholders and encourage them to keep shares instead of selling, which leads to the evaporation of those banks. Keywords: Financial Performance, Islamic Banks, Stock Prices. JEL Classifications: C18, G21 DOI: https://doi.org/10.32479/ijefi.9157